Eurasian Civilization in the Context of the Great Silk Road Logistics - I. V. Boiko (Евразийская интеграция: экономика, право, политика, 2021)
The significance of the Great Silk Road is interesting not only by its history, but by the knowledge, required for the better understanding of the current economic and political realities as well. The introduction of the new insights into the essence of the Eurasian trade route, its emergence and destruction studied under the projection on the contemporary processes, undermining the global supply chain represents the main idea of the given research. In the article, the Great Silk Road is represented in the logistics framework: generation of the freight flows, peculiarity of their material composition, the pathway trajectory architecture, creation of the necessary infrastructure. The significance of the spatial peculiarity, natural preconditions and advanced technologies for the freight generation, the international trade development and the Eurasian civilization emergence is emphasized. The paper reveals special logistic characteristics of silk as the initial chain in the ancient trade as well as the distinctive characteristics of transportation mode and freight. The political stability plays a significant role in the risk reduction for the freight turnover and for functioning of the international transportation system in general. The endogenous and exogenous reasons for the Great Silk Road breakdown are related with the increasing trade deficit between the East and West, the import substitution policy accepted by the European countries and increasing protectionism in their external trade relations. Exploring the Great Silk Road downfall, the author concludes about the contemporary global supply chain disruption causes, emphasizing the negative impact of the economic and political influence. The US-China trade war destroys the international trade. The COVID-19 pandemic tends the business localization. Ecological threats provide new requirements to the freight flows. The “pull strategy”, practiced by the logistic companies is steadily replacing by the “push strategy”. Moreover, China has been reducing investments into the trans-Eurasian project. That kind of instability could lead to a deep transformation of the international transportation systems as well as the system of the international relations in general. Russia should consider those new realities carefully when scheduling its international division of labour strategy.